7 ( x - 1 ) - 2 ( x - 5 ) = x - 5
alguém ajuda por favor..
Soluções para a tarefa
Respondido por
0
Resposta: -2
Explicação passo a passo:
7 ( x - 1 ) - 2 ( x - 5 ) = x - 5
7x - 7 - 2x + 10 = x - 5
7x - 2x - x = - 5 + 7 - 10
4x = -8
x = -8/4
x = -2
Respondido por
0
Faz a distributiva:
Resposta: x = -2
Perguntas interessantes
Português,
7 meses atrás
História,
7 meses atrás
Direito,
7 meses atrás
Matemática,
7 meses atrás
Português,
7 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás